Phospate Release Study on Silica Gel and Amino Silica Hybrid Sorbent from Lapindo Mud - Ade I. Agipa; Muhamad F. Muarif (Jurnal Akademika Kimia, 2022)
This study discusses the rate of phosphate release in Silica Gel (SG) and Amino Silica Hybrid (ASH) sorbents using Lagergren pseudo-first Order Kinetic and Lagergren Pseudo-second Order Kinetic. ASH synthesis was done by adding a 3-aminopropyltriethoxysilane (APTES) modifier to sodium silicate from Lapindo Mud. Phosphate binding was carried out at 30 minutes with a stirring speed of 250 rpm. Analysis using IR spectrophotometer showed the success of ASH synthesis as indicated by the appearance of functional groups -NH2 and -CH2 at wavenumbers 1635 cm-1 and 1473 cm-1. With the continuous method, SG and ASH sorbents that have bound phosphate were then desorbed at various times of 2, 3, 4, 7, 8, and 9 days. The amount of phosphate anion released from SG and ASH was tested using a UV-Vis instrument then modeling was carried out to determine the rate of phosphate release. The desorption results showed the amount of phosphate released from the ASH sorbent was less than that of the SG sorbent. Through modeling, the proceeds of the phosphate release rate follow the Lagergren Pseudo-second Order Kinetic with an experimental QE of 0.22089 M/g for SG sorbent and 0.33333 M/g for ASH sorbent.